Association of Malabsorption and Anaemia in Adults in Tertiary Care Hospital - Hussain, Altaf; Hafeez, Muhammad; Naveed, Muhammad; Shah, Syed Umer; Khan, Muhammad Shahid; Cheema, Ahmed Ammar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association of malabsorption in celiac disease with anaemia and other sociodemographic factors at a tertiary care hospital in Pakistan.Study Design: Cross sectional studyPlace and Duration of Study: Department of General Medicine Military Hospital Rawalpindi from Jul to Dec 2019.Methodology: A total of 300 adults were included in the study, 150 cases were patients with the diagnosis of celiac disease, and the other 150 were controls without celiac disease. Celiac disease was diagnosed based on biopsy findings by a consultant gastroenterologist. Defined was defined based on haemoglobin levels. In addition, the relationship between age, gender, anaemia, and the presence of comorbidities was assessed with the presence of celiac disease among the adults included in the study.Results: Out of 300 cases and controls, 116 (38.7%) patients were males, and 184 (61.3%) were females. One hundred and forty-eight (49.3%) did not show the presence of anaemia, while one hundred and fifty-two (50.7%) showed the presence of anaemia. we found a statistically significant difference in cases and controls regarding the presence of comorbidities and the presence of anaemia (p